The Relevance of the Islamic Education Curriculum to the Needs of Students in the Industrial Revolution 4.0 Era (Study at ABA Sleman Kota Kindergarten): Relevansi Kurikulum Pendidikan Islam dengan Kebutuhan Peserta Didik di Era Revolusi Industri 4.0 (Studi di TK ABA Sleman Kota) - Kusumastuti, Vivi; Mawardi, Imam (Prosiding University Research Colloquium, 2023)
The rapid development of information technology is often assumed to have an impact on the formation of a new culture and a society with a new personality. The world of education duringthe industrial revolution 4.0 faces a generation born in a period of technological development. They are generation Z and Alpha or commonly called digital natives. Currently, ABA Sleman Kota Kindergarten applies an Islamic education curriculum which is a combination of the 2013 curriculum which is integrated with Al-Islam, Kemuhammadiyahan, and Keaisyiyahan. The purpose of the study was to see how ABA Sleman KotaKindergarten applies the Islamic education curriculum to the needs of students in the 4.0 era. The time of this study is in May 2023. This research is a research with a qualitative descriptive approach. Data collection techniques in the form of documentation, observation, interviews. Data analysis can use an interactive data analysis model consisting of three components. Thethree components are: (1) data reduction, (2) display, and (3) drawing conclusions and verifying.From the research, it was obtained that the Islamic education curriculum in ABA Sleman Kota Kindergarten is still very relevant to the needs of students in the 4.0 era. Theimplementation of the Islamic education curriculum in ABA Sleman Kota Kindergarten is carried out with a central learning model that implements STEAM through the use of loose parts. The project method is an option when learning so that children are free to realize imagination while realizing the concept of independent play. Independentconceptions playing with project methods can also be done in the central learning model. In addition, to adjust to the needs of students in the 4.0 era, guru has made efforts to harmonize the implementation of the Islamic education curriculum as evidenced by the results of the evaluation of learning outcomes. Thus, the Islamic education curriculum applied at ABA Sleman Kota Kindergarten is still relevant to the needs of students in the era of the industrial revolution 4.0.